Livre, porém servo/a e louco/a por Jesus: a produção do/a jovem cristão/ã no Currículo da Célula Evangelizadora - Gislene Rangel Evangelista (2023)
In this thesis it is analyzed how the juvenile produces themselves in the Evangelizing Cell Curriculum. The production of the self is a Foucauldian’s theory discussion which comprehends that the subject is constituted through practices of governing others and self-government, so that in the production of oneself the focus of the discussion is on the ethical work which the subject carries out on themselves, in order to constitute their own as the moral subject of its actions. I investigated the juveniles involved in one protestant religious practice known as Cell. Considering the relationship between the youth and cyberculture, an Instagram page called a.rede was also investigated. I name the set of practices that happened in the cell's face-to-face meetings and the interactions in the a.rede as Evangelizing Cell Curriculum. Curriculum, in turn, is understood as discursive, that is, as productive practices that are formed under regimes of truth about the protestant christian faith. As methodology, the research articulated elements and procedures of ethnographic, netonographic and asceticism as foucauldian analytics, as a theoretical-methodological tool. The thesis here developed is that in the Evangelizing Cell Curriculum the christian juvenile is produced as free, but servent and crazy about Jesus, through self-denial practices, obedience, holiness, liberty and love. Free, but servant and crazy about Jesus are subject positions named by myself from the analysis of the taught practices in the investigated curriculum. The characteristics and the way how the young christian should be conducted are taught through the practices that they should operate on themselves and through them lead their own existence. Practices of self-denial, holiness, liberty and love are outputted by a regime of truth which certify that to have access to God the juvenile should be distinct, waiving the cultural and social standards of the world they live in.